Dynamic binding of the bacterial chaperone Trigger factor to translating ribosomes in Escherichia coli - Tora Hävermark; Mikhail Metelev; Erik Lundin; Ivan L. Volkov; Magnus Johansson (Proceedings of the National Academy of Sciences, 2025)
The bacterial chaperone Trigger factor (TF) binds to ribosome-nascent chain complexes (RNCs) and cotranslationally aids the folding of proteins in bacteria. Decades of studies have given a broad, but often conflicting, description of the substrate specificity of TF, its RNC-binding dynamics, and competition with other RNC-binding factors, such as the Signal Recognition Particle (SRP). Previous RNC-binding kinetics experiments were commonly conducted on stalled RNCs in reconstituted systems, and consequently, may not be representative of the interaction of TF with ribosomes translating mRNA in the cytoplasm of the cell. Here, we used single-particle tracking (SPT) to measure TF binding to actively translating ribosomes inside living Escherichia coli . In cells, TF displays distinct binding modes—longer (ca 1 s) and shorter (ca 50 ms) RNC bindings. Consequently, we conclude that TF, on average, stays bound to the RNC for only a fraction of the translation cycle. Further, binding events are interrupted only by transient excursions to a freely diffusing state (ca 40 ms), suggesting a highly dynamic binding and unbinding cycle of TF in vivo. We also show that TF competes with SRP for RNC binding, and in doing so, tunes the binding selectivity of SRP.